Observations of black carbon and albedo over a Central Himalayan Glacier (Satopanth): Preliminary results. (May 2021) - Sandeep, K.; Panicker, A.S.; Gautam, Alok Sagar; Safai, P.D.; Beig, G.; Nainwal, H.C.; Bisht, D.S.; Das, S.
Abstract: Simultaneous measurements of ambient atmospheric black carbon (BC) mass concentrations and radiative fluxes were carried out over Satopanth glacier in the central Himalayas from September 22 to October 2, 2016, as a part of a glacier campaign experiment. The daily mean atmospheric BC concentrations varied between 165 ± 20–263 ± 32 ng m −3 with a mean of 199 ± 54 ng m −3 during the observational period. The measured average surface albedo was found to be 0.24 ± 0.11 during the entire period of observation. Spectral albedo from Moderate Resolution Imaging Spectroradiometer - Bidirectional Reflectance Distribution Function (MODIS-BRDF) satellite observation and net radiometer derived glacier albedo was found to be in good agreement with a correlation of 0.64 over the region. Concentration weighted trajectory analysis (CWT) over the site indicates a 70% BC transport from the Indo-Gangetic plain, Pakistan, and the Middle East region. BC radiative forcing was estimated using an optical model along with a radiative transfer model. An average BC direct radiative forcing of −5.4 ± 0.25 W m −2 and 2.4 ± 0.19 W m −2 was found respectively in the surface and at the top of the atmosphere (TOA) during the experimental period. The estimated average BC induced heating rate was found to be 0.33 ± 0.04 K day −1 over the region. Highlights: BC mass varied between 165 and 263 ng m −3 over Satopanth glacier. The measured surface albedo was 0.24 ± 0.11 over the glacier. Local and long-range transport was identified as BC sources. The average BC atmospheric forcing was +7.8 W m −2 over the region.